4-Hydroxy-trans-2-nonenal (4-HNE) induces neuronal SH-SY5Y cell death via hampering ATP binding at kinase domain of Akt1 - Kashyap, M.; Singh, A.; Yadav, D.; Siddiqui, M.; Srivastava, R.; Chaturvedi, Vishal; Rai, N. (Springer, 2015)
Inhibition mechanism(s) of protein kinase B/Akt1 and its consequences on related cell signaling were investigated in human neuroblastoma SH-SY5Y cells exposed to 4-hydroxy-trans-2-nonenal (4-HNE), one of the most reactive aldehyde by-products of lipid peroxidation. In silico data indicate that 4-HNE interacts with kinase domain of Akt1 with the total docking score of 6.0577 and also forms H-bond to Glu234 residue similar to highly potent Akt1 inhibitor imidazopiperidine analog 8b, in which the protonated imidazole nitrogen involves in two hydrogen bonds between Glu234 and Asp292. The strong hydrogen bonding with Glu234 and hydrophobic interactions with several residues, namely Leu156, Gly157, Val164, Ala177, Tyr229, Ala230, Met281 and Thr291, at the vicinity which is normally occupied by the ribose of ATP, appear to be the main causes of Akt1 inhibition and lead to the significant conformational change on this region of protein. Results of mutational docking prove that Glu234 plays a major role in 4-HNE-mediated Akt1 inhibition. In silico data on Akt inhibition were further validated by observing the down-regulated levels of phosphorylated (Thr308/Ser493) Akt1 as well as the altered levels of the downstream targets of pAkt, namely downregulated levels of pGSK3ß (Ser9), ß-catenin, Bcl2 and upregulated levels of pro-apoptotic markers, namely Bad, Bax, P53 and caspase-9/3. The cellular fate of such pAkt inhibition was evidenced by increased reactive oxygen species, degraded nuclei, transferase dUTP nick end labeling positive cells and upregulated levels of pJNK1/2. We identified that 4-HNE-mediated Akt1 inhibition was due to the competitive inhibition of ATP by 4-HNE at the kinase domain of ATP binding sites.